The roles of directors in corporate governance in the 21st century Nigeria (2021)
The Company is referred Io as a legal person distinct from the shareholders. Company have the attributes/qualities of human beings, however it has been rightly described as a legal abstraction, an artificial person who enjoys such Status as a consequence of its incorporation. A Company, though a “legal Personality" has no mind or will of its own. Its action, of a necessity must be found in some persons who are the directing mind and will of the Company. They give directives as to the day to day running of the activities of the Company. They are not in themselves the Company but they are appointed to direct the affairs of the Company. These set of people are called the Company’s directors and as a body, is usually referred to as „Board of Directors". The success or failure of a Company largely depends on its board of directors. The roles of the directors have over the years been amplified in the 21" Century, such that directors now shoulders higher responsibility, a departure from its core traditional duties and liabilities. This paper therefore examines the roles of directors in the modern day Company s management and administration and suggested ways of enhancing their impact on the sustainability of Company’s development.